Estudo das propriedades vibracionais e estruturais do cristal de ácido succínico em condições extremas de temperatura e pressão - Santos, Yuri Gomes dos (2024)
Succinic acid is an organic compound belonging to the class of dicarboxylic acids, widely used as a precursor for various chemicals of economic and technological interest. Despite its extensive application, the lack of detailed information on its physical properties under extreme conditions motivated the undertaking of this dissertation. In this study, irregular prism-shaped single crystals of succinic acid were grown by the slow solvent evaporation method at room temperature. Powder X-ray diffraction measurements confirmed that the sample is in the β phase, which has a monoclinic structure belonging to the P21/c space group, with two molecules per unit cell (Z=2). The vibrational spectrum was obtained using Raman spectroscopy, and the vibrational modes at room temperature were assigned using Potential Energy Distribution (PED) based on computational calculations utilizing Density Functional Theory (DFT). Experimental results as a function of temperature, including Raman scattering, thermal analyses, and single-crystal X-ray diffraction, revealed the structural stability of the sample in the range from 12 K to 291 K. At high temperatures, modifications in the Raman spectrum around 423 K were interpreted as a phase transition, later confirmed by thermal analyses. High-pressure Raman spectroscopy, using nujol as the pressure-transmitting medium, was conducted from ambient pressure up to 7.3 GPa, revealing that the sample does not undergo a structural phase transition within the investigated pressure range. However, changes were observed in the vibrational modes associated with the O3 and O12 atoms, which participate in hydrogen bonding, suggesting a reorganization of these interactions.